Serviceability limit state design of large concrete structures: Impact on reinforcement amounts and consequences of design code ambiguity. (15th December 2019) - Basteskår, Mikael; Engen, Morten; Kanstad, Terje; Johansen, Håvard; Fosså, Kjell Tore
Highlights: SLS control of concrete can result in unexpected additional reinforcement amounts. Results from SLS checks of concrete shells vary with load complexity. The variation is due to the amount of choices pertinent to the calculation methods. A parametric study of additional reinforcement from SLS checks is proposed. The SLS checks in Eurocode 2 can give several hundred percent increased demand. Abstract: Reinforced concrete is typically designed taking into account the critical load combination in the ultimate limit state (ULS), while further checked in the serviceability limit state (SLS). Experience shows that the SLS control can result in unexpected additional reinforcement amounts. This paper investigates this topic through ( i ) a case study and ( ii ) a parametric study. In the case study, different methods are used to check a cross section subject to membrane and plate forces. We found significant variation in the results using different methods, due to the amount of choices pertinent to the methods. The variation in results was found to increase with increasing load complexity. The parametric study shows the amount of additional reinforcement necessary due to crack width requirements compared to ULS design. The crack width requirements in Eurocode 2 is shown to require a relative increase of several hundred percent in reinforcement compared to ULS design, and an absolute increase, as a percentage of the effective concrete area, of 9%. We conclude that there are large discrepancies in subjective understanding of the crack width limitation requirements as well as in interpretation of the code provisions and calculation methods.